2019
DOI: 10.3389/fchem.2019.00447
|View full text |Cite
|
Sign up to set email alerts
|

Clustering-Triggered Emission of Carboxymethylated Nanocellulose

Abstract: Non-conjugated polymers with luminescence emission property have recently drawn great attention due to their promising applications in different areas. Most traditional organic synthetic non-conjugated polymers required complicated synthesis. Herein, we report a non-conjugated biomass material, carboxymethylated nanocellulose (C-CNC), which is found to be practically non-luminescent in dilute solutions, while being highly emissive when aggregated as nanosuspensions. We propose that the luminescence of C-CNC or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 55 publications
3
45
0
Order By: Relevance
“…2,25,26 The autofluorescence of poly-and oligo-saccharides, from various sources, has previously been widely reported. 6,[27][28][29][30][31][32][33][34][35] This autofluorescence is generally attributed to contamination of the sample with aromatic compounds, i.e. lignin, or proteins, dependent on the source.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,25,26 The autofluorescence of poly-and oligo-saccharides, from various sources, has previously been widely reported. 6,[27][28][29][30][31][32][33][34][35] This autofluorescence is generally attributed to contamination of the sample with aromatic compounds, i.e. lignin, or proteins, dependent on the source.…”
Section: Introductionmentioning
confidence: 99%
“…6,31 In relation to cellulosic nanomaterials with typical surface chemical modifications, Li et al investigated the autofluorescent properties of carboxymethylated nanocellulose. 33 They demonstrated that the particles exhibited two fluorescent bands with an approximate wavelength difference of 40 nm, the second of which increased with concentration. This second peak was attributed to electron transitions between oxygen n orbitals and the carboxyl π* orbitals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because CTE does not require conjugated groups, it has many advantages over emission from traditional aromatic conjugated molecules, such as facile synthesis, good water solubility, and low biological toxicity 9,[11][12][13][14] . For this reason, CTE has become the potent alternative for the conventional one in many fields, such as color tunable light-emitting [15][16][17][18][19][20] , room-temperature phosphorescence [11][12][13][14][21][22][23][24][25][26] , as well as bioimaging and chemical sensing 13,[22][23][24][27][28][29][30] . It would be very promising if CTE is able to replace traditional emission in an even vast number of fields.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of polymeric nanoparticles with AIE property by simple extraction of renewable natural raw material would be very attractive, which was paid little concern. Biomass resources have been extensively studied because of their excellent properties such as wide sources, non-toxic, renewable and so on (An et al, 2019 ; Du et al, 2019 ; Li et al, 2019c ), in addition, they are also used as raw materials for the preparation of fluorescent materials due to their own sustainability (He et al, 2018 ; Li et al, 2019b ). Larch bark is typically regarded as waste, but larch bark extracts (LBE) contain large amounts of catechol-containing compounds (Jiang et al, 2014 , 2016 ; Luo et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%